KESEJAHTERAAN LANSIA DAN BEBERAPA FAKTOR YANG MEMPENGARUHI DI DESA DANGIN PURI KAUH - Tanaya, Raka Riani; Murjana Yasa, I Gusti Wayan (PIRAMIDA; Vol 11 No 1 (2015): Jurnal PIRAMIDA, 2015)
Indicators of success of development is the increasing life expectancy of the population. The purpose of this study was to determine the effect of religiosity , economic conditions , and access to health simultaneously and partially to the welfare of the elderly in Dangin Puri Kauh . Then the sample was taken 86 of the total 624 elderly seniors who are in Dangin Puri Kauh . This study used quantitative analysis techniques namely multiple linear regression analysis . Based on the results of the study , obtained information that Religiosity ( X1 ) , Economics ( X2 ) , and Health ( X3 ) , has a significant effect simultaneously and partially on the elderly Welfare ( Y ) on Dangin Puri Kauh . This means that the higher the religiosity ( X1 ) , Economics ( X2 ) , and Health ( X3 ) owned by the elderly , the elderly Welfare Kauh Dangin Puri Denpasar will increase .
Keywords: eldery welfare; religiosity; economics, health